The orchestra: convivence and education within prisons - Pierre Lassus, Marie- (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
The aim is to show how the orchestra could be a convivence “milieu” and an education place that is able to restore confidence and self-esteem to convicts and improve the living together in prisons. The study is based on the research-action methodology (qualitative-quantitative) and the research-creation to show that the learned values inside the orchestra (listening,  responsibility, discipline, solidarity, convivence), can be apply in everyday’s life and can initiate a processus of change by introducing each other to new possibilities that facilitate reintegration into social life. In the context of French prisons characterised nowadays by a growing overcrowding causing conflicts and violence, or within Venezuelan prisons where these problems are repeated, the creation of orchestra is a political project aimed to establish a personal and community aera where convicts can interact in these places dedicated to separation and fragmentation of spaces and time. In conclusion, education cannot take place without the creation of a friendly “milieu”(in the meaning given by the international convivialist movement) where the principles of individualization and creative opposition are asserted, which are at the foundation of any true democracy as well as the orchestra conceived as a micro-society.